Training and retention in rural and remote Australia: Examining the association between GP vocational training placements and subsequent practice location in Western Australia. (August 2021) - Makate, Marshall; Ledwith, Tonia; Robinson, Suzanne; Broderick, Isabel; Miller, Sonia; Bell, Janice
Abstract: This paper aims to provide insights on the association between exposure to rural general practice vocational training placements and subsequent rural practice location in Western Australia. We further explore the possibility that the observed associations might depend on an individual's rural upbringing and or an individual's exposure to general practice during medical school. To this end, a cross-sectional analysis of practice location of 353 general practitioners who completed their vocational training through WA General Practice Education and Training between 2010 and 2017 was conducted. The empirical analysis uses a fully recursive conditional mixed process estimator to jointly estimate the probabilities that a general practitioner (GP) completes their vocational training placement at a rural location and subsequently practices at a rural location. The results show that GPs who chose rural locations for their first and last vocational training placements are more likely to practice at a rural location compared to their counterparts choosing metropolitan locations. Also, the probability of subsequent rural practice is further strengthened by having a rural background and having exposure to general practice during medical school even after controlling for potential confounders. The results also indicate that GPs stay in rural locations for reasons linked to their career, family and lifestyles. This evidence underscores the importance of vocational training organisations in WA and reinforces the need for ongoing rural opportunities in training to ameliorate location-based disparities in the distribution of the GP workforce in Western Australia. Highlights: We examined the association between GP vocational training placement and subsequent practice location in Western Australia. Evaluated the joint influence of a rural upbringing and prevocational exposure to general practice on rural practice. GP vocational training placements in rural and remote areas strongly predict subsequent rural practice. A rural background in sync with prevocational exposure to general practice increases the probability of rural practice.